Penerapan Naïve Bayes Dan Visualisasi Wordcloud Dalam Analisis Sentimen Pengguna E-Learning - Narasati, Riri; Solehudin, Dodi (CV. Multi Kreasi Media, 2023)
This study aims to analyze the sentiment of e-learning users using the Naïve Bayes method and WordCloud visualization. In today's digital era, e-learning has become an increasingly popular learning platform, making sentiment analysis of users on this platform crucial to understand their experiences. The Naïve Bayes method was chosen for classifying user sentiment, while WordCloud visualization is used to display the frequency of words appearing in user reviews. The data used in this research were collected from user comments and reviews on e-learning platforms. The results indicate that the Naïve Bayes method is effective in classifying user sentiment, while WordCloud provides a clear representation of the most frequent words in the reviews, revealing the sentiment patterns present.